β Cell–specific increased expression of calpastatin prevents diabetes induced by islet amyloid polypeptide toxicity - Gurlo, Tatyana (JCI Insight, 2016)
The islet in type 2 diabetes (T2D) shares many features of the brain in protein misfolding diseases. There is a deficit of β cells with islet amyloid derived from islet amyloid polypeptide (IAPP), a protein coexpressed with insulin. Small intracellular membrane-permeant oligomers, the most toxic form of IAPP, are more frequent in β cells of patients with T2D and rodents expressing human IAPP. β Cells in T2D, and affected cells in neurodegenerative diseases, share a comparable pattern of molecular pathology, including endoplasmic reticulum stress, mitochondrial dysfunction, attenuation of autophagy, and calpain hyperactivation. While this adverse functional cascade in response to toxic oligomers is well described, the sequence of events and how best to intervene is unknown. We hypothesized that calpain hyperactivation is a proximal event and tested this in vivo by β cell–specific suppression of calpain hyperactivation with calpastatin overexpression in human IAPP transgenic mice. β Cell–specific calpastatin overexpression was remarkably protective against β cell dysfunction and loss and diabetes onset. The critical autophagy/lysosomal pathway for β cell viability was protected with calpain suppression, consistent with findings in models of neurodegenerative diseases. We conclude that suppression of calpain hyperactivation is a potentially beneficial disease-modifying strategy for protein misfolding diseases, including T2D.